Jurisprudential Analysis of the Nature of Money Creation with an Emphasis on Mudaraba on Debt in the Banking System - Sadegh Elham; Mohammad Mahdi Shariatinejad; Muhammad Rasul Fakhreh (تحقیقات مالی اسلامی (پیوسته))
Money creation in the banking system is an important phenomenon, the quality and manner of which creates many effects in the economic system. Therefore, the analysis of many banking issues such as mudarabah depends on the nature and dimensions of money creation. Economists in their analysis of the process of money creation have defined it with two approaches: multiplier and endogenous money creation (money creation from nothing). Proponents of the multiplier approach define money creation as an operation dependent on deposits, and on the other hand, another group does not accept the dependence on deposits in money creation and believe that banks can create credit only by granting loans. . The nature of money created in the banking system and the effects and consequences of banking contracts, especially in mudarabah, along with issues that require research and study; Because the analysis of debt from bank created money has caused the challenge of mudarabah on debt, which is invalid from the point of view of most jurists, and hence banking mudarabah suffers from problems. This article, which is compiled with a descriptive and analytical method, is trying, since debt or commodity nature of money creation has serious effects on usury-free banking, it first adopts the basis of debt or commodity nature of money creation and then examines Permissibility or non-permissibility of debt mudarabah, apply these contents and draw a conclusion. Finally, after the investigations, this research confirms the validity of such a transaction with the money created by the banking system, emphasizing the famous ruling on the inadmissibility of mudarabah on debt.